Penilaian Tingkat Kematangan Tata Kelola Teknologi Informasi menggunakan CobIT 4.1 pada PT XYZ - Fransiska Prihatini Sihotang (Ikatan Ahli Informatika Indonesia (IAII), 2018)
PT XYZ is one of the companies in Indonesia that produces cement and has 3 factories spread across the region. This company has long utilized Information Technology (IT) in supporting its business process, but not yet know the level of maturity of the IT application because it has not been measured yet. Measuring the level of maturity of IT governance is important to do, so that management knows the extent to which IT governance helps management to achieve organizational goals. Measurement of IT governance can be done if it is known what processes should be measured. Measurement of the value of IT governance maturity in PT XYZ using COBIT 4.1 framework. Data collection was done by interview, literature study, observation, and questionnaire. The result of this research is known that IT governance at PT XYZ is at the third level (defined process).